Psychogenic Equinovarus Caused by Dislocation of the Chopart Joint Complex - Ichiro Tonogai; Koichi Sairyo (Case Reports in Orthopedics)
Patients with conversion disorder (CD) present with weakness or unexplained movement disorder that may evolve from inciting psychological events, but presentation with rigid deformity is rare. Only one case of CD presenting as foot deformity with atraumatic rigid psychogenic equinovarus has been reported previously. Here we describe a rare case of psychogenic equinovarus in a physically healthy 10-year-old boy. He had noticed left equinovarus deformity upon waking abruptly but had no history of preceding trauma and no relevant medical history. Computed tomography (CT) images revealed dislocation of the left Chopart joint complex, but clinical examination did not suggest an organic neurologic disorder. On further history taking, he reported that he was under psychological stress because of being required to play baseball against his will. When he was given permission to withdraw from this stressful situation, the equinovarus improved without the need for surgical invention. This report highlights the importance of early and accurate diagnosis of psychogenic equinovarus, so that unnecessary surgery can be avoided. This is the first report of psychogenic equinovarus caused by dislocation of the Chopart joint complex that was confirmed with CT.